Industrial training report: Perlis State Secretary Office - Ku Rusli, Ku Muhammad Fakhruddin (Universiti Teknologi MARA, Perlis, 2024)
SWOT analysis for the Perlis State Secretary Office provides a comprehensive overview of the organization's strategic positioning. During my industrial training, I performed a SWOT analysis of the Perlis State Secretary Office, which provides an in-depth understanding of the organization's current state and prospective future directions. The effective governance and decision-making processes that are fostered by strong administrative frameworks and good leadership are among the strengths noted. But there are also significant flaws, such outdated systems and technology that restrict responsiveness and operating effectiveness. The office's inability to upgrade has a major impact on its capacity to adjust to the constantly changing needs of government. There are many opportunities, especially when it comes to using digital transformation to improve public participation and service delivery. Adopting cutting-edge technology could enhance data management, expedite processes, and promote improved public relations. Strategic alliances and joint ventures with other governmental and non-governmental organisations may also improve the office's resources and skills. Nonetheless, the report also identifies a few risks, such as the public's dissatisfaction which may undermine trust in the office's capacity to run state affairs. This opinion emphasises how urgently better community participation and public relations campaigns are needed to regain and maintain public confidence. Thus, even while the Perlis State Secretary Office has potential and strengths of its own, it will remain ineffective and irrelevant in serving the people of Perlis unless its technological flaws are addressed and public unhappiness is reduced. For the office to successfully manage the difficulties and seize the possibilities found in this SWOT analysis, proactive efforts in these areas will be crucial.